BIBLIOMETRIC ANALYSIS OF THE DEEP ROOTS OF ECONOMIC DEVELOPMENT LITERATURE - Mbangezeli, Sinawo; Phiri, Andrew (International Journal of eBusiness and eGovernment Studies, 2023)
There is an increasing consensus amongst economist that patterns of modern-day growth may be influenced by historical artefacts or 'deep root factors' which existed centuries before our modern civilizations. The purpose of our study is to provide a bibliometric analysis on the extensive body of studies surrounding the 'deep roots' literature with the aim of understanding the patterns of research on the topic. We analyse 695 documents collected between 1993 and 2023 using the biblioshiny function of bibliometrix package of R-studio to map and analyse the bibliometric data. The analysis yielded the following findings: The subject has gained significant interest since the early 1990s, with most studies being conducted by researchers and collaborations in industrialised countries and institutions. Furthermore, the authors who have developed various measures of'deep root' variables are the most productive and highly cited. These studies are typically published in top-tier economic journals. Key terms such as 'Africa', 'economic development', 'economic growth', and 'inequality' are commonly used in the current literature. These findings lead us to identify areas for future research. Expanding the scope of literature on deep roots to include diverse contemporary outcomes improves our understanding of a country's overall performance and can provide strong evidence to support the importance of historical factors in policymaking. The recommendations derived from these findings highlight the significance of increased inclusivity and collaboration in the deep roots' literature.